Health Professionals' Attitudes Towards Using a Web 2.0 Portal for Child and Adolescent Diabetes Care: Qualitative Study - Nordqvist, Cecilia; Hanberger, Lena; Timpka, Toomas; Nordfeldt, Sam (JMIR Publications, 2009)
Background The Internet, created and maintained in part by third-party apomediation, has become a dynamic resource for living with a chronic disease. Modern management of type 1 diabetes requires continuous support and problem-based learning, but few pediatric clinics offer Web 2.0 resources to patients as part of routine diabetes care. Objectives To explore pediatric practitioners' attitudes towards the introduction of a local Web portal for providing young type 1 diabetes patients with interactive pedagogic devices, social networking tools, and locally produced self-care and treatment information. Opportunities and barriers related to the introduction of such systems into clinical practice were sought. Methods Twenty clinicians (seven doctors, nine nurses, two dieticians, and two social welfare officers) from two pediatric diabetes teams participated in the user-centered design of a local Web 2.0 portal. After completion of the design, individual semi-structured interviews were performed and data were analyzed using phenomenological methods. Results The practitioners reported a range of positive attitudes towards the introduction of a local Web 2.0 portal to their clinical practice. Most interviewees were satisfied with how the portal turned out, and a sense of community emerged during the design process and development of the portal's contents. A complementary role was suggested for the portal within the context of health practice culture, where patients and their parents would be able to learn about the disease before, between, and after scheduled contacts with their health care team. Although some professionals expected that email communication with patients and online patient information would save time during routine care, others emphasized the importance of also maintaining face-to-face communication. Online peer-to-peer communication was regarded as a valuable function; however, most clinicians did not expect that the portal would be used extensively for social networking amongst their patients. There were no major differences in attitudes between different professions or clinics, but some differences appeared in relation to work tasks. Conclusions Experienced clinical practitioners working in diabetes teams exhibited positive attitudes towards a Web 2.0 portal tailored for young patients with type 1 diabetes and their parents. The portal included provision of third-party information, as well as practical and social means of support. The practitioners' early and active participation provides a possible explanation for these positive attitudes. The findings encourage close collaboration with all user groups when implementing Web 2.0 systems for the care of young patients with chronic diseases, particularly type 1 diabetes. The study also highlights the need for efforts to educate clinical practitioners in the use of Web publishing, social networking, and other Web 2.0 resources. Investigations of attitudes towards implementing similar systems in the care of adults with chronic diseases are warranted.